2013
DOI: 10.3109/00365521.2013.800993
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic colitis in Uppsala health region, a population-based prospective study 2005–2009

Abstract: The incidence of MC in Uppsala health region is similar to other studied areas. The majority of patients had a self-limiting or easily treated condition, but 14% need a more or less continuous medication. Ten percent of the patients demonstrate other symptoms than chronic watery diarrhea. The possibility of concomitant celiac disease should be considered in new cases of MC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 25 publications
5
50
0
4
Order By: Relevance
“…Population studies have shown an increasing incidence of MC over recent decades, with a mean incidence rate of 1.1-7.0/100,000 inhabitants for CC and an incidence rate of 3.1-5.5/100,000 inhabitants for LC [Fernandez-Banares et al 1999;Olesen et al 2004b;Pardi et al 2007;Vigren et al 2012;Thörn et al 2013]. The increased incidence has stabilized over the past years, and the incidence is associated with female gender and increasing age [Gentile et al 2014].…”
Section: Epidemiologymentioning
confidence: 93%
See 3 more Smart Citations
“…Population studies have shown an increasing incidence of MC over recent decades, with a mean incidence rate of 1.1-7.0/100,000 inhabitants for CC and an incidence rate of 3.1-5.5/100,000 inhabitants for LC [Fernandez-Banares et al 1999;Olesen et al 2004b;Pardi et al 2007;Vigren et al 2012;Thörn et al 2013]. The increased incidence has stabilized over the past years, and the incidence is associated with female gender and increasing age [Gentile et al 2014].…”
Section: Epidemiologymentioning
confidence: 93%
“…MC in this context should be considered as a part of the original IBD disease, and not as a separate entity [Jegadeesan et al 2013]. Furthermore, these changes can also be found in persons without any signs of gastrointestinal symptoms or diseases [Wang et al 1988;Thörn et al 2013]. Altogether, there is no histopathological hallmark that differentiates primary, idiopathic MC from a MC evolved secondary to another syndrome or its treatment, or that differentiate MC in healthy subjects from patients with symptoms.…”
Section: Histopathologymentioning
confidence: 99%
See 2 more Smart Citations
“…The largest retrospective cohort population study conducted to date did not report any association between MC and IBD [2]. What is more, one prospective population-based cohort study, conducted by Thörn et al [3], specifically aimed to address the potential bidirectional relationship between IBD and MC, including all new diagnoses of both IBD and MC during 2005-2009, also failed to document any significant correlation between the two conditions.…”
Section: Linkage Between Ibd and MCmentioning
confidence: 99%